Grant of Joint Property to Children Through Private Deed (Analysis of Decision Number 287 PDT.G/2022/PA/MDO) - Ahmad, Imran; Hi Arsad, Jamal; Faisal, Faisal; Junaidi, M (Dinasti Research, 2025)
This research’s title is Grant of Joint Property to Children Through Private Deed (Analysis of Decision Number 287 PDT.G/2022/PA/MDO). The object of this research is Derden Verzet (Third Party Resistance) case Number 287Pdt.G/2022/PA/Mdo at the Manado Religious Court, Indonesia. The objective of this research is to analyze whether joint property that has been donated through a private deed remain joint property or the child's personal property and the strength of the evidence of a private deed in granting joint property to a child at the Manado Religious Court. This study uses a normative juridical legal research type with a statute approach and a case approach. The results of the study show that in the Manado Religious Court Decision Number 287Pdt.G/2022/PA/Mdo, the Judge confirmed that joint assets that have been donated to children through a private agreement are still recognized as valid, thus the joint assets that have been donated are no longer included in joint assets but rather the property of the children as recipients of the grant. The private deed of grant of joint assets from the Defendants to the Opponents has the power of proof because it is recognized as signed by Defendant II as the party who signed it.